Urgensi Manajemen Konflik dalam Meningkatkan Kualitas Lembaga Pendidikan Islam - Nurul Anisa Rahmadia; Halimatus Sabila; Herman Junaidi Nasution; Merza Azanni; Anaas Tri Ridlo Dina Yuliana (Jurnal Pendidikan Islam, 2022)
Conflict is an inseparable part of human life. When conflict is seen as a lesson, the conflict will become a force for progress. Not all conflicts in Islamic education institutions are detrimental. Many existing conflicts have beneficial influences and impacts if appropriately managed. If a conflict occurs in an Islamic educational institution, then this can be a lesson from his mistakes and bring good afterward. However, the conflict will also be a weakness that can cause stress, division, and even hostility. This research discusses the urgency of conflict management in improving the quality of Islamic Education Institutions using the literature study research method. This method analyzes books, journals, magazines, and articles related to the problem and research objectives. Data collection techniques are carried out by researchers with editing, organizing, and finding. The study results show that conflict management in Islamic educational institutions is the ability to control conflicts that require specific management skills. In Islam, conflict is not a goal, but a means to unite conflicting things and liberate human life from individual interests and vices so they can be brought to the right path. Thus, conflict management is essential to achieve goals and improve the quality of Islamic educational institutions.